KERAGAAN VEGETATIF DAN KOMPONEN TANDAN DARI SILANG BALIK SEMU PERTAMA Elaeis oleifera ORIGIN BRAZIL DAN SURINAME DI SUMATRA UTARA, INDONESIA - Heri Adriwan Siregar; Hernawan Yuli Rahmadi; Retno Diah Setiowati; Edy Suprianto (Pusat Penelitian Kelapa Sawit, 2018)
An Attempt to combine the superior traits of Elaeis oleifera and Elaeis guineensis have been done through an interspecific hybrid cross and followed by pseudo-backcross 1 (pBC1). Observation of vegetative morphology and bunch components are presented in this paper. Two populations of pBC1 E. oleifera from the Suriname and Brazil origin were planted in 1990, 1993, 1995, and 2005, and were intensively observed for vegetative morphological properties and bunch components in November 2016 to February 2018. The results showed that almost all the individuals of pBC1 grew upright such as E. guineensis, no longer growing horizontally like the wild E. oleifera and the interspecific hybrid populations. The datas showed that the Suriname population plant architecture are compact or smaller than the Brazilian origin including the height increment and the size of the stem, the frond architecture and its components. Similarly, the bunch components show that the pBC1 Brazil is slightly superior to Suriname pBC1.